Memories, recollections, and landmarks or how I became a pioneer - JALOBEANU, Mihai Stanislav (Studia Universitatis Babeș-Bolyai Digitalia, 2017)
The paper presents a pioneering period (68-76) in the context and with the difficulties of those years remembered all of a sudden in 2006 on the celebration of Herbert Francke in Bremen. This led without further explanations to a partial restart of the educational activity in the ‘graphic-imagery’.